Characterization of epoxy/steel fibres composites for hybrid injection moulds - Leite, Janaina L. (2013)
Metallic fibres in polymeric matrix are used for mouldings blocks of hybrid injection moulds improving the mechanical and thermal properties. This paper reports on the characterization of epoxy resin/short steel fibres (SSF) composites. The effect of the concentration of 2,4,6-tris (dimethylamino- methyl) phenol as accelerator in the epoxy system was evaluated by viscosity and dynamical mechanical analyses. The composites were characterized by compression and microhardness tests. The fibres dispersion into the epoxy matrix was analysed by optical microscopy. It was found that the best accelerator concentration for this type of composite was 5,0 parts by weight.